THE USE OF AUTHENTIC MATERIALS IN ESP CLASSES FOR VOCATIONAL PROGRAM OF MEDICAL LABORATORY TECHNOLOGY - Erlinna Juita, (JOEL: Journal of Educational and Language Research, 2023)
In the digital era, English is essentially needed for communication. Therefore, English for Specific Purposes is required, especially in vocational program. The ESP class is designed to prepare the students to be able to use English related to their field of study. However, learning resources in medical laboratory technology are difficult to find. the purpose of this study is to improve the students’ vocabulary mastery in ESP classes through the use of authentic materials, Classroom Action Research was conducted in two cycles at Akademi Kesehatan John Paul II Pekanbaru. The samples of the study were the students taking ESP classes. The results of the study indicated the improvement of students’ vocabulary mastery. The students obtained the average score of 41.52, 54.39, and 72.98 in the pre-research, cycle 1, and cycle 2 respectively. The students also perceived that the use of authentic materials had been successfully brought the real language in medical laboratory into the classroom. In conclusion, the use of authentic materials could improve the students’ vocabulary in the ESP class and create learning experience